Analysis of the accuracy and completeness of cardiovascular health information on alcohol industry-funded websites. (4th September 2021) - Peake, Lewis; van Schalkwyk, May C I; Maani, Nason; Petticrew, Mark
Abstract: Background: The Alcohol Industry (AI), and the Social Aspects/Public Relations Organisations (SAPRO) it funds, has been shown to mis-represent the risk of alcohol with respect to cancer and pregnancy. It is theorized that the AI would position alcohol as 'heart healthy' to further undermine public perceptions of risks from drinking. Methods: A comparative analysis (including content, thematic and context analyses) of cardiovascular health information published on the websites of AI-funded ( n = 18, such as 'Drinkaware' and the 'Distilled Spirits Council of the US') and non-AI-funded ( n = 18, such as 'NHS.uk') organizations based in multiple high-income jurisdictions. Results: Websites of non-industry-funded health organizations were more likely than AI/SAPRO websites to label alcohol as a risk factor for a range of important cardiovascular diseases (such as myocardial infarction, congestive cardiac failure, hypertension and stroke). Conversely, AI/SAPRO websites were more likely to suggest alcohol was protective in the development of some heart conditions. AI/SAPRO websites frequently referenced the J-shaped curve as proof of benefit from moderate alcohol consumption; suggested a balance between the benefits and harms from drinking; positioned alcohol as consistent with a 'healthy lifestyle'; and framed drinking as a social norm. Conclusions: AI-funded health organizations mis-represent the evidence on cardiovascular effects of moderate alcohol consumption. Healthcare professionals should appreciate the role of funding source in biasing content, and exercise caution when directing patients to content funded by the AI. Tighter regulation of messaging that AI/SAPRO's provide to the public is required, to avoid the dissemination of harmful misinformation.